EVOLUTIONARY TRENDS AND STASIS IN MOLAR MORPHOLOGY OF RHAGAPODEMUS-RHAGAMYS LINEAGE IN THE PLEISTOCENE OF SARDINIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2012)
Stasis, random walk and directional evolutionary patterns have been tested on the lower and upper first molars of the Rhagapodemus-Rhagamys lineage (Rodentia, Muridae) from Middle and Late Pleistocene fissure fillings of Monte Tuttavista, Orosei, Sardinia, Italy. We recorded the maximum length/maximum width ratio and size on 252 lower first molars and 208 upper first molars belonging to different fossil samples of Rhagapodemus minor and Rhagamys orthodon in order to explore evolutionary dynamics underlying molar morphology evolution. Akaike Information Criterion (AICc) was used for selection of the best model of evolution, in order to distinguish different evolutionary patterns. Our results clearly show that Rhagapodemus-Rhagamys lineage undergoes stasis during the middle and late Pleistocene of Sardinia, while size shows a random walk pattern between populations, characterized by an increase in size at the Rhagapodemus minor-Rhagamys orthodon transition.
Keywords: murid molars; Sardinia; Pleistocene; morphometrics; modes of evolution; stasis; random walk